Montessori mealtimes for dementia: A pathway to person-centred care. (May 2022) - Cartwright, Jade; Roberts, Karen; Oliver, Elizabeth; Bennett, Michelle; Whitworth, Anne
Purpose: This study examined the impact of a Montessori mealtime intervention for people living with dementia to support the mealtime experience of residents and mealtime care practices of staff in a memory support unit. The mealtime intervention was part of a broader culture change project. Method: An observational research design was used to evaluate changes in the mealtime experience and care practices across three time points (baseline, post-implementation, maintenance), spanning 30 months. Five video recordings of the lunch time service (range: 19–32 min) were analysed. The coding protocol comprised pre-determined indicators related to accepted dimensions of person-centred care. Resident and staff behaviours were quantified across four categories: providing choice and preferences, promoting the social side of eating, supporting independence and showing respect towards residents. Staff behaviours that reflected personal enhancing actions and personal detractors were also coded during each mealtime service. Results: A significant increase in staff providing residents with the opportunity for choice and a subsequent significant increase in residents demonstrating choice behaviours was evident. Staff and residents both significantly increased their interactional behaviours, with greater social interaction between staff and residents. Staff further demonstrated greater support for mealtime independence that reached and maintained significance during the final two sampling points. Significant gains observed post implementation were largely maintained and, on specific measures, further increased over time. A significant increase in staff use of personal enhancing actions during mealtime care was also evident. Variability in individual staff and resident behaviour highlighted the complexity of mealtime care and culture change processes. Implications: The study provides novel evidence to support the use of a Montessori mealtime intervention to achieve more person-centred mealtime care, and which resulted in a more respectful, enabling and social dining experience. Clinical implications and direction for future research are presented to build on these findings.